POTENSI STIMULASI SENSORIK GAMMA NONINVASIF PADA PASIEN GERIATRI DENGAN PENYAKIT ALZHEIMER: TINJAUAN LITERATUR: NON-INVASIVE GAMMA SENSORY STIMULATION POTENTIAL IN GERIATRIC ALZHEIMER’S PATIENTS: A LITERATURE REVIEW - Amanda, Samira; Ihsan, M.; Nurdiansyah, M.; Perawati (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Alzheimer's disease (AD) is one of the common health problems faced by the elderly, which can affect cognitive abilities and brain function. Currently available therapies are not very effective in managing AD in some people, so there is still a need for other treatment innovations in improving the QoL of patients. So this innovation presented with the aim to exploring the effectiveness of gamma sensory stimulation in preventing white matter atrophy and myelin loss, and its impact on cognitive decline. This research is a literature review sourced from several internet search engines. The review conducted through several stages, including identification, screening, and fulfillment inclusion and exclusion criteria, and finally resulting in 7 articles. The use of this device as therapy in geriatric patients with AD has been clinically tested and shown positive results in overcoming white matter atrophy and myelin loss in geriatric patients with AD. By improving these conditions, the device has the potential to slow the progression or even reduce symptoms experienced by patients, such as cognitive decline. Thus, based on the findings of this study, gamma stimulation could be a potential complementary therapy for Alzheimer's patients, thereby improving their quality of life. AbstrakPenyakit alzheimer (AD) merupakan salah satu masalah kesehatan yang sangat sering dihadapi oleh lansia (usia 60 tahun keatas), yang dapat mempengaruhi kemampuan kognitif serta fungsi otak. Terapi yang tersedia saat ini belum begitu efektif dalam mengelola AD pada beberapa orang, sehingga masih diperlukan inovasi pengobatan lainnya dalam meningkatkan kualitas hidup pasien. Sehingga inovasi ini dihadirkan dengan tujuan untuk mengeksplorasi efektivitas stimulasi sensorik gamma dalam mencegah atrofi materi putih dan kehilangan mielin, serta dampaknya terhadap penurunan kognitif. Penelitian ini merupakan kajian pustaka yang bersumber dari beberapa mesin pencari internet. Kajian dilakukan melalui beberapa tahap, meliputi identifikasi, penyaringan, dan pemenuhan kriteria inklusi dan eksklusi, sehingga menghasilkan 7 artikel yang memenuhi kriteria inklusi. Penggunaan alat ini sebagai terapi pada pasien geriatri dengan AD telah teruji secara klinis dan menunjukkan hasil yang positif dalam mengatasi atrofi materi putih dan kehilangan mielin pada pasien geriatri dengan AD. Dengan memperbaiki kondisi ini, alat ini berpotensi memperlambat progresi atau bahkan mengurangi gejala yang dialami pasien, seperti penurunan kognitif. Sehingga, berdasarkan temuan kajian ini, stimulasi gamma bisa menjadi terapi pelengkap yang potensial untuk pasien Alzheimer, sehingga meningkatkan kualitas hidup pasien.